Native and engineered extracellular vesicles for wound healing - Lu, Shengli; Lu, Liping; Liu, Yang; Li, Zenan; Fang, Yuan; Chen, Zhizhao; Zhou, Jianda (Frontiers in Bioengineering and Biotechnology, 2022)
Extracellular vesicles (EVs) that act as messengers mediate communication between parent and recipient cells through their contents, including nucleic acids, proteins and lipids. These endogenous vesicles have emerged as a novel cell-free strategy for the treatment of wounds. Various types of cells can release EVs with unique biological properties. Recent studies have shown that native EVs are used as therapeutic agents to promote tissue repair by participating in all physiological processes of wound healing. Furthermore, the content and surface of EVs can be designed, modified, and engineered to improve their specificity, safety, and efficiency for wound healing. The engineering strategies of EVs are divided into the parent cell modification and indirect modification of EVs. The therapeutic potential of current EVs and engineered EVs for wound healing still requires the exploration of their large-scale clinical applications through innovative approaches. Herein, we provide an overview of the current biological knowledge about EVs and wound healing, as well as the application of native EVs in promoting wound healing. We also outline recent advances in engineering EV methodologies to achieve ideal therapeutic potential. Finally, the therapeutic applications of engineered EVs in wound healing are reviewed, and the prospects and challenges for the translation of engineered EVs to clinical applications are discussed.